Orthogeriatrics in Italy: the Gruppo Italiano di Ortogeriatria (GIOG) audit on hip fractures in the elderly - Amedeo Zurlo (Geriatric Care, 2018)
The Gruppo Italiano di Ortogeriatria (GIOG) is an Italian study group promoted by three Italian Scientific Geriatric Societies with the aim of disseminating orthogeriatric methodology in Italy. In 2015 it has supported a multicenter web-based audit to collect data on functioning of Italian orthogeriatrics. The study, still ongoing, has enrolled until now 2577 cases of elderly patients undergoing surgery for hip fracture from 14 Italian orthogeriatric units. The population in question consists of markedly elderly and frail subjects, due to high prevalence of pre-existing functional deficit conditions, but it is also clinically complex; the most frequent fracture is intertrochanteric and the most performed surgery approach is intramedullary nail. This is the largest multicenter observational study conducted so far in Italy on elderly patients with hip fracture.